Studies on Synthesis and Antimicrobial Activity of Some Falvonols - Subbanwad, G.R.; Vihbute, Y.B. (Asian Journal of Chemistry, 2010)
Flavonols are synthesised from 1-(2´-hydroxy-simple/substituted phenyl)-3-(simple/substituted-1-naphthyl)-2-propene-1-ones by oxidation with alkaline hydrogen peroxide solution (Algar-Hynn-Oyamada reaction). These flavonols are characterised by elemental analysis and spectral study. All these compounds were screened for their antimicrobial activity against bacteria (E. coli and S. aureus) and fungi (C. lunata and H. oryzae). In few compounds the results are found to be encouraging.